Advanced Morphological and Functional Magnetic Resonance Techniques in Glaucoma. (8th June 2015) - Mastropasqua, Rodolfo; Agnifili, Luca; Mattei, Peter A.; Caulo, Massimo; Fasanella, Vincenzo; Navarra, Riccardo; Mastropasqua, Leonardo; Marchini, Giorgio
Abstract : Glaucoma is a multifactorial disease that is the leading cause of irreversible blindness. Recent data documented that glaucoma is not limited to the retinal ganglion cells but that it also extends to the posterior visual pathway. The diagnosis is based on the presence of signs of glaucomatous optic neuropathy and consistent functional visual field alterations. Unfortunately these functional alterations often become evident when a significant amount of the nerve fibers that compose the optic nerve has been irreversibly lost. Advanced morphological and functional magnetic resonance (MR) techniques (morphometry, diffusion tensor imaging, arterial spin labeling, and functional connectivity) may provide a means for observing modifications induced by this fiber loss, within the optic nerve and the visual cortex, in an earlier stage. The aim of this systematic review was to determine if the use of these advanced MR techniques could offer the possibility of diagnosing glaucoma at an earlier stage than that currently possible.